Perancangan Aplikasi Silogisme Artikel Bahasa Batak Dengan Menerapkan Metode Textrank - Martha Munthe (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Communicating with each other is one of the basic human traits. Communication serves as a means of interacting with one another. Humans sometimes want to master one foreign language. Especially if that language is popular. Humans also don't want to be outdated in mastering the language. dictionary then humans will be able to learn the language and know what language they want to master. So far, if someone wants to learn a foreign language, one example is Korean, the medium used to facilitate vocabulary mastery is through a dictionary. Because the dictionary form is still in the form of like books, inflexible, difficult to carry, resulting in less effective when out or on the road. A practical and effective new media such as smartphone media is needed because smartphones support various applications such as dictionary applications. The dictionary application on the smartphone does not search for words manually. But the search facility in the dictionary application makes it easier for users to get the words they want to look for. one of the string matching algorithms such as the text rank algorithm, it makes it easier and faster to search for words in the dictionary. It was explained that the Textrank Algorithm begins to match the pattern at the beginning of the text. Word matching starts from the left position until finally reaches the rightmost position, this algorithm will match the character of the pattern character with the characters in the corresponding text, until one of the following conditions is met, namely the character in the pattern and in the text being compared does not match (mismatch) and all the characters in the pattern match, then the algorithm will notify the discovery at this position.